THE GRAMMATICAL HUNTING: STRATEGI KREATIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA DALAM BAHASA ARAB (STUDI KASUS DI KELAS VII D Mts 2 SIDOARJO) - Siti Anisatul Azizah; Wulan Indah Fatimatul Djamilah; Syafiul Naqsya Bandiy (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
This study aims to evaluate the effectiveness of the application of the Grammatical hunting strategy in improving the reading ability of class VII D students of MTsN 2 Sidoarjo. This study uses a qualitative approach with a descriptive design, data collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles and Huberman. The Grammatical hunting strategy is implemented through activities to search for grammatical elements (fi'il, isim, and huruf) in the text that actively involve students, followed by group discussions and presentations of the analysis results. The research findings show a significant increase in students' ability to identify grammatical elements, from 29% to 73.5%, as well as an increase in reading comprehension completion reaching 61%. In addition, this strategy is proven to be able to foster critical thinking skills, strengthen motivation, and create more interactive learning. Thus, Grammatical hunting can be recommended as an effective, innovative learning method to improve the reading skills and grammatical comprehension of Arabic language students in Islamic junior high schools. The application of this method is expected to be a reference for educators to design more creative, participatory, and sustainable learning, as well as open up opportunities for further research in different educational contexts and levels.